2020
DOI: 10.1186/s12981-020-00307-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of survival pattern and its predictors among HIV positive patients on highly active antiretroviral therapy in Southern Ethiopia public health facilities: a retrospective cohort study

Abstract: Background: In resource poor countries like Ethiopia, little is known about the survival of patients treated with antiretroviral therapy which depends on different factors. Evidence shows that mortality has been high particularly in the first 3 to 6 months of initiating antiretroviral therapy. Hence, the study aimed to assess the Epidemiology of survival pattern and its determinants among adult HIV positive patients on highly active antiretroviral therapy. Methods: Retrospective cohort study was employed among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 18 publications
6
11
6
1
Order By: Relevance
“…Patients with baseline ambulatory or bedridden functional status were about two fold at higher risk of death within the first year of HAART as compared to patients with working functional status at enrolment to ART (AHR = 2.18; 95% CI: 1.01, 4.74). This finding is agreed with other studies conducted in different parts of Ethiopia at different time periods, India, and China [20,28,29,[35][36][37][38][39]. This is due to the fact that ambulatory or bedridden functional status is an indicator of low immune status.…”
Section: Plos Onesupporting
confidence: 92%
“…Patients with baseline ambulatory or bedridden functional status were about two fold at higher risk of death within the first year of HAART as compared to patients with working functional status at enrolment to ART (AHR = 2.18; 95% CI: 1.01, 4.74). This finding is agreed with other studies conducted in different parts of Ethiopia at different time periods, India, and China [20,28,29,[35][36][37][38][39]. This is due to the fact that ambulatory or bedridden functional status is an indicator of low immune status.…”
Section: Plos Onesupporting
confidence: 92%
“…Likewise, the hazard of adult mortality was 9.58 times higher among adults with poor drug adherence than adults who had good adherence to ART (AHR=9.58, 95% CI: 8.72–30.97). This is consistent with other studies in Nekemet, 22 Kambata Tambaro Zone 16 (AHR = 3.8, 95% CI: 1.88, 7.96) Goffa zone, 13 Canada. 23 …”
Section: Discussionsupporting
confidence: 93%
“…In this cohort, 7.65% (95% CI: 5.21–10.42) patients have died. This is in line with other studies in Aksum hospital (8.85%) 8 Oromia region (10.3%), 9 Eastern Ethiopia (5.9%), 10 Tigray central zone (7.5%), 11 Jinka hospital (10%), 12 Gofa zone hospital (7.5%) 13 and Latin America (7.3%). 14 However, this finding is lower than studies in Hiwot Fana teaching hospital (11.9%), 15 Kambata tambaro zone (12.63%), 16 Malawi (12.6%), 17 Durban, South Africa (16%) 18 and India (13%, 16.1%).…”
Section: Discussionsupporting
confidence: 92%
“…It was found that the patients who started ART in older age (> 45 years) have a 2-fold higher risk of dying than those who baseline age was within 15 and 30 years (AHR = 2.10; 95% CI: 1.41-3.12%). Other studies done across many parts of Ethiopia also reported same results that patients with older age have higher risk of mortality compared to those with younger age patients enrolled on ART [9,11,13,26]. This could be due to the fact that individuals are at higher risk of complications and respond poorly to ART, as a result of combined effect of aging, HIV infection, and antiretroviral treatment.…”
Section: Discussionmentioning
confidence: 68%
“…The present study has shown that patients having concomitant TB infection had almost a 2-fold higher risk of mortality than those who did not present with concomitant TB infection during follow-up period (AHR = 1.79; 95% CI: 1.39-2.31%). Several studies performed across many parts of Africa and Ethiopia have reported that past TB co-infection at baseline was associated with high level of mortality among patients on ART [9][10][11][12][13][14][15]. Indeed, a study conducted in Cameroon indicated that patients with past TB co-infection showed 2.35-times more risk of death than those who without TB co-infection [16].…”
Section: Discussionmentioning
confidence: 99%